Phylogeography and genetic connectivity of the marine macro‐alga Sargassum ilicifolium (Phaeophyceae, Ochrophyta) in the northwestern Pacific1. Issue 1 (29th December 2018) - Ng, Poh‐Kheng; Chiou, Yu‐Shan; Liu, Li‐Chia; Sun, Zhongmin; Shimabukuro, Hiromori; Lin, Showe‐Mei
Abstract : The evolutionary influences of historical and contemporary factors on the population connectivity and phylogeographic structure of a brown seaweed, Sargassum ilicifolium, were elucidated using the nuclear ITS2 and mitochondrial COI markers for the collections newly sampled within its distribution range in the northwestern Pacific (NWP). Significant genetic structure at variable levels was identified between populations (pairwise F ST ) and among populations grouped by geographical proximity (ΦCT among regions). The adjacent groups of populations with moderate structure revealed from AMOVA appeared to have high genetic connectivity. However, a lack of genealogical concordance with the geographic distribution was uncovered for S. ilicifolium from the NWP. Such genetic homogeneity is interpreted as a result of the interaction between postglacial recolonization and dynamic oceanic current regimes in the region. Two separated glacial refugia, the South China Sea and the Okinawa Trough, in the marginal seas of east China were recognized based on the presence of endemic haplotypes and high haplotype diversity in the populations at southern China and northeast of Taiwan. Populations persisting in these refugia may have served as the source for recolonization in the NWP with the rise of sea level during the warmer interglacial periods. The role of oceanic currents in maintaining genetic connectivity of S. ilicifolium in the region was further corroborated by the coherence between the direction of oceanic currents and that of gene flow, especially along the eastern coast of Taiwan. This study underlines the interaction between historical postglacial recolonization and contemporary coastal hydrodynamics in contributing to population connectivity and distribution for this tropical seaweed in the NWP.